Drivers of nutrient content and spatial variability of soil multifunctionality in the topsoil of Kyrgyzstan - Chen, Yusen; Zhang, Shihang; Li, Huiliang; Wang, Yongdong (Frontiers in Environmental Science, 2022)
In this paper, we used field sampling data in Kyrgyzstan to investigate the spatial variability and distribution of soil nutrients and soil multifunctionality (SMF) within different soil depths and its driving factors in the country by using factor analysis, combined with structural equation modeling (SEM). The findings of this research study indicated firstly that the topsoil of Kyrgyzstan (0–30 cm) stores 4.24±0.59 Pg of SOC, 0.33±0.06 Pg of total nitrogen (TN), 0.31±0.03 Pg of total phosphorus (TP), and 5.12±1.84 Pg of total potassium (TK). The nutrient reserves of various land-cover categories vary greatly across the nation, with grasslands accounting for the largest reserves (40 %) but urban areas allocating the smallest proportion (0.3%). Secondly, the analysis revealed that using the linear or nonlinear fitting equations, the majority of soil nutrients exhibited a strong correlation with each other and also environmental parameters; thirdly, in Kyrgyzstan, SMF varied substantially from –0.63 to 2.30 across regions. Fourthly, according to the SEM results, NPP, wind speed (VS), MAP, longitude (Lon), SWC, and pH directly affected SMF. In addition, several indirect effects of ST, MAT, Sard, and latitude (Lat) on SMF were observed. Lon, map, SWC, and pH also had various direct and indirect impacts on SMF. The findings of this study shed light on the functions of the entire soil ecosystem in the Kyrgyz Republic that help better predict the effects of environmental changes on ecosystem multifunctionality in drylands and provide a scientific basis for rational utilization of soil resources, efficient management of dryland soils, and prevention of land productivity decline in the country.